EKOLOGI BERBASIS SYARIAH: ANALISIS WACANA KRITIS PEMIKIRAN MUDHOFIR ABDULLAH - Maghfur Ahmad (Jurnal Hukum Islam, 2015)
This study aims at analyzing Mudhofir Abdullah's thought on environmental conservation as the final aim of sharia. Up to present, there have been five principles of sharia, al-maqasid al-syari‘ah, which includes nurturing religion, souls, dignity, wealth and descendants. Environmental problems (al-bi‘ah) have never been included in the analysis of al-maqasid al-syari‘ah. Through literature study with critical discourse analysis approach, the results of this study indicate that: (1) Al-Quran as a source of knowledge, provides insights and discusses ecological and environmental issues, (2) as a religious text, verses in Al quran which deal with ecological and environmental issues should be contextually understood by employing eco-ushulfiqh; and (3), without ecological and environmental guarantee, al-maqasid al-syari‘ah may not be able to be achieved. Therefore, according to Mudhofir's thought, ecological and environmental issues should be the top concern in sharia. Within Islamic study context, Mudhofir has broadened the horizon on how Islamic teaching can answer the challenge of ecological and environmental problems within society.